Performance Level of Physical Education Students: Basis for the Development of Task-Based Teaching Strategies - Abegail B. Limbo; Charis B. Limbo-Rivera (Indonesian Journal of Physical Education and Sport Science)
Study purpose. In teaching Physical Education (PE), one must have a repertoire of suitable teaching strategies to facilitate learners' competencies. Thus, this study aims to determine the performance level of the Grade 10 PE students and the extent of implementation of the Grade 10 PE curriculum in Mahaplag, Leyte Division, with the end view of designing a task-based teaching strategy in Physical Education.